S60 Risk factors associated with mycobacterium tuberculosis (MTB) infection and progression to active TB disease in child contacts. (14th November 2013) - Karnani, N; Sridhar, S; Connell, D; Lalvani, A
Abstract : Background: Mathematical modelling has shown the most effective strategy to eliminate tuberculosis (TB) worldwide is to address the large burden of latent TB infection (LTBI). Identification of the risk factors which predispose individuals to acquire Mtb infection and those determining risk of progressing from infection to active disease will enable risk stratification for targeted TB interventions. Objective: To identify host, socioeconomic and environmental risk factors for acquiring Mtb infection following exposure to TB and risk factors for progression from infection to active TB disease. Methods: Risk factors associated with infection and progression were investigated in a primary analysis of a well-defined cohort of 965 Turkish household child contacts exposed to smear positive pulmonary TB patients. Risk factors for infection were assessed in study subjects with and without Mtb infection. Mtb infection was defined by interferon gamma-release assay (IGRA) results at two time points–baseline and 6 months–thus creating robust criteria to avoid misclassification of IGRA converters and IGRA reverters. Adjusted odd ratios were estimated using stepwise logistic regression including variables with p < 0.2 on univariate regression. Results: In the child cohort passive smoking was found to be an independent risk factor for Mtb infection (OR: 1.52, 95% CI: 1.09 –2.12). Higher household monthly income was an independent protective factor against Mtb infection (OR: 0.55, 95% CI: 0.38 –0.79). Increasing age was associated with a decreased risk of progressing from infection to disease (OR: 0.67, 95% CI: 0.51–0.87). Children exposed to more than 1 TB patient were 8 times more likely to progress to disease (OR: 8.66, 95% CI: 1.54–48.55). Conclusion: Identification of an association between passive exposure to cigarette smoke and acquisition of Mtb infection in children adds new evidence for smoking cessation strategies to be incorporated into TB prevention programmes. To aid TB elimination we therefore advocate an enforcement of stricter tobacco control policies, particularly in regions with a high burden of TB.